Party Cadreization and Political Communication Pattern: A Comparative Study of PKS and Gerindra In West Sumatera - Afdhalur Rahmat; Suryanef Suryanef; Fatmariza Fatmariza; Al Rafni (Yayasan Darussalam Bengkulu, 2026)
The Partai Keadilan Sejahtera (PKS) and the Gerakan Indonesia Raya (Gerindra), two prominent political parties in West Sumatra, have cadre development programs. This study examines these programs' effects on organizational sustainability and election results. Despite using quite distinct cadre-building strategies, both parties remained competitive in the West Sumatra Provincial Legislative Elections of 2019 and 2024. In-depth interviews with nine key informants, including party cadres, executives, and political observers, were used in conjunction with document analysis of internal policies and training initiatives as part of a qualitative comparative approach. The analysis framework incorporates Randall and Svåsand's (2002) metrics of systemness and value infusion in addition to Huntington's (1968) four aspects of party institutionalization (adaptability, complexity, autonomy, and coherence). Results show that PKS's methodical, hierarchical cadre training cultivates cadres with strong ideological commitment, steadfast allegiance, and continuous constituent involvement, resulting in a consistent rise in votes from 389,526 in 2019 to 453,572 in 2024. The vote reduction from 476,985 (2019) to 427,177 (2024) is correlated with Gerindra's flexible, experience-driven methodology, which prioritizes electoral mobilization over organized value inculcation. These different routes highlight how party cohesion, resilience, and long-term electoral viability are influenced by the caliber of cadre development. Parties that prioritize systematic value-based training tend to produce stronger institutionalization and more durable structures over electoral cycles, however no single model is always better.